Observation, the police and public administration: introduction - Fleming, Jenny (2008)
This conversation about the merits of ethnography in police studies began at the `Ethnography in Policing' panel at the Political Studies Association Conference held in Leeds in 2005. Subsequent correspondence and occasional one-to-one meetings led to this symposium. - Reproduced.
Keywords: Police; Public administration